Outcomes From Re-Treatment and Cerebrospinal Fluid Analyses in Patients With Syphilis Who Had Serological Nonresponse or Lack of Seroreversion After Initial Therapy. Issue 6 (June 2021) - Zhang, Xiaohui; Shahum, Andrea; Yang, Li-Gang; Xue, Yaohua; Wang, Liuyuan; Yang, Bin; Zheng, Heping; Chen, Jane S.; Radolf, Justin D.; Seña, Arlene C.
Abstract : Background: We conducted an observational study to determine whether patients with syphilis who do not demonstrate serological cure or lack of seroreversion in nontreponemal (NT) antibody titers after initial therapy benefit from re-treatment and cerebrospinal fluid (CSF) analysis. Methods: We enrolled patients with syphilis from sexually transmitted disease clinics in Guangzhou, China, who had persistent NT titers after therapy. Serological nonresponse was defined as a <4-fold decline in baseline NT titers after therapy. Lack of seroreversion was defined as demonstrating a ≥4-fold NT titer decline but without seroreversion to negative, or having persistent low-level titers (i.e., 1:1–1:2) after therapy. After consent, we abstracted medical record data regarding syphilis diagnoses, initial and re-treatment regimens, and serological outcomes. Nontreponemal titers were obtained from participants at enrollment and follow-up. We evaluated CSF findings among a subgroup of participants relative to re-treatment. Results: From March 2012 to February 2016, we enrolled 135 HIV-negative patients with syphilis with persistent NT titers after initial therapy. Among 116 participants with ≥12 months of follow-up, 60 (52%) received re-treatment of syphilis. Overall, there were no significant differences in serological response between those who were re-treated and those who were not among serological nonresponders (29% vs. 27%; P = 1.0) or among participants without seroconversion (41% vs. 37%; P = 0.8). Of 60 participants who underwent CSF analyses, 8 (13%) had CSF abnormalities, but only 2 (3%) met the neurosyphilis criteria after re-treatment. Conclusions: Most HIV-negative patients with syphilis who have serological nonresponse or lack of seroreversion after therapy do not benefit from re-treatment in the short term, and neurosyphilis is uncommon. Abstract : A study conducted among 116 HIV-negative patients with syphilis in China who had serological nonresponse or lack of seroreversion after initial therapy demonstrated no benefits from re-treatment, and neurosyphilis is uncommon.